A Review of "The Challenge of Modernity, the Quest for Authenticity in the Arab World " - Ahmad Biglari; Ebrahim Barzegar (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The purpose of this book is to find the answer to the failure of the modernization project in the Middle East. He does this by tracing the fundamental contradictions of the culture of the region. Louay Safi reviewed the formation of the mentality of development in ideas of Descartes and Kant, then he discussed the comparison of two theoretical models of Marxian and Weberian development. He, through giving priority to structures of knowledge and culture, clarified his position on this matter. The author has analyzed the notion of intellectuals in the Muslim world since the beginning of facing with two layers of the Western modern civilization, the colonial and technological progress. He tried to analyze Arab and Muslim scholars' exposure to the problem of tradition-modernity through showing how they deal with the Islamic and Arabic heritages. Safi, finally, believed that a local development would be achieved by means of an active and a critical return to the Arab Islamic heritage; and the path of development leads not only to the West. Although the author has claims that he has gone beyond the Western models, in the end, he has just presented an overall view, namely the need to refer to the heritage development. Therefore, this work can only be considered as an entry in necessity of the local development. Furthermore, it can also be seen as a methodological confusion and discord in the book.